Kostum Tjokroaminoto dalam Mendukung Setting Ruang dan Waktu pada Film Guru Bangsa: Tjokroaminoto - Syaifatul Ais Salam; Cito Yasuki Rahmad (Texture:Art and Culture Journal, 2023)
Costume design is an important part of artistic direction and plays a crucial role in supporting a film's setting and time period. This study focuses on the costumes worn by the main character, Tjokroaminoto. The film's setting ranges from Tjokroaminoto's teenage years to his adulthood, and the costumes used create an authentic atmosphere during that time period. The research method used is qualitative research, using primary and secondary data sources obtained from interviews, observations, and literature studies. After the data is collected, data analysis is carried out through the process of reduction, presentation, conclusion drawing, and verification. The results show that the film's historical setting, "Guru Bangsa: Tjokroaminoto," is effectively conveyed through the costumes worn by the characters, which help to express space, time, social status, and three-dimensional character. Tjokroaminoto's costume consists of several parts such as basic clothing, headwear, bodywear, footwear, and accessories. The costume worn by Tjokroaminoto portrays a priyayi who comes from the Javanese region with a division of the time period when the story takes place.